SUMMARY: NEEDS AND OPPORTUNITIES FOR MANAGING TURKEY POPULATIONS - Laurence R. Jahn (Wildlife Society Bulletin)
This national meeting has served as an important vehicle for exchanging information on problems, advances, and opportunities in turkey research and management. All 41 speakers and participants in the discussions contributed important information. My purpose is to identify (1) outstanding progress in research and management, and (2) future needs to maintain and restore turkey populations in an environment dominated by man. For convenience, my remarks will focus on four topics: (1) the status of turkeys, (2) census and other techniques, (3) harvest management, and (4) habitat management.